2013
DOI: 10.1021/jp312613r
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Structure of Graphite Oxide through Ammonia Treatment for Photocatalytic Generation of H2 and O2 from Water Splitting

Abstract: Graphite oxide (GO) synthesized from the oxidation of graphite powders exhibits p-type conductivity and is active in photocatalytic H 2 evolution from water decomposition. The p-type conductivity hinders hole transfer for water oxidation and suppresses O 2 evolution. Treating GO with NH 3 gas at room temperature tunes the electronic structure by introducing amino and amide groups to its surface. The ammonia-modified GO (NGO) exhibits n-type conductivity in photoelectrochemical analysis and has a narrower optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 85 publications
7
97
0
1
Order By: Relevance
“…Electronic structural analysis revealed that graphene oxide (GO) materials have conduction band minimum (CBM) and valence band maximum (VBM) levels suitable for generating H 2 and O 2 , respectively, under visible-light irradiation [80]. Size modulation and chemical modification readily tune the electronic properties of graphene.…”
Section: Photocatalyst For Overall Water-splitting [79]mentioning
confidence: 99%
“…Electronic structural analysis revealed that graphene oxide (GO) materials have conduction band minimum (CBM) and valence band maximum (VBM) levels suitable for generating H 2 and O 2 , respectively, under visible-light irradiation [80]. Size modulation and chemical modification readily tune the electronic properties of graphene.…”
Section: Photocatalyst For Overall Water-splitting [79]mentioning
confidence: 99%
“…This could be helpful for highly active photocatalytic processes. [ 43,56 ] It also renews the understanding of role of oxygen-containing functional groups in GO and its part-reduced derivatives. Moreover, a greater understanding of the fundamental physics of carbon nanomaterials will eventually be a benefi t for design and fabrication of novel carbon-based nano optical-electronic devices in the not-too-distant future.…”
mentioning
confidence: 93%
“…This bandgap is close to the recent analysis results from incident photon to current conversion effi ciency and linear potential scans of GO. [ 43 ] Therefore, this kind of unusual bleaching signal mode directly indicates the bandgap of GO. This also means that ultrafast broadband transient absorption spectroscopy excited in visible light range can be used for detecting the bandgap of GO as well as rGO (see below).…”
mentioning
confidence: 97%
“…GO exhibits p-type conductivity because of oxygen's high electronegativity compared to carbon. Likewise, n-type conductivity appears when graphene covalently bonds to electron donating nitrogen-containing functional groups [1]. As oxygen bonds to graphene, the valence band originates from the O 2p orbital rather than the π orbital of graphene, leading to a larger band gap for a high oxygen coverage rate of GO and thus an evolution from semimetal to insulator.…”
Section: Go As a Photocatalystmentioning
confidence: 99%
“…Meanwhile, the conduction band of GO is mainly contributed by the anti-bonding π* orbital, which has a higher energy level than that needed for H 2 generation [2]. Therefore, GO with an appropriately functionalization might be a promising photocatalyst [1][2][3][4][5][6][7].…”
Section: Go As a Photocatalystmentioning
confidence: 99%